Students’ and Lecturers’ Experience in English Medium Instruction (EMI) Classrooms: A Qualitative Study in Social Science Programs - Rinia Zatalini; Rifki Oktoviandry; Riskha Hanifa Nasution; Salam Mairi; Hengki Agus Rifai (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
English has been adopted as a medium of instruction in international classes at Universitas Negeri Padang (UNP) for around six years now. However, research examining its use is very rare. This study then aims to investigate the experience of lecturers and university students using English medium instruction in international classes at UNP seen from six aspects. The study focused on undergraduate social science programs in four faculties. Nine lecturers and eight students were chosen through purposive sampling technique to participate. Semi-structured interviews were carried out to obtain data for this descriptive qualitative study. Data were analysed using thematic analysis. Generally, the result reveals that (1) the teaching and learning are conducted bilingually; (2) lecturers use the same method while teaching in the EMI and non-EMI classes & focus on the content not the language; (3) both students and lecturers have difficulty in using English to interact; (4) the use of English has, to some extent, developed the participants’ English skills; (5) there is lack of support to improve the English skills of both participants, thus (6) trainings on how to enhance the English skills of both lecturers and students are necessary.